Incidence, mortality and survival of prostate cancer in two municipalities with a high human development index in Mato Grosso - Evangelista, Flávio de Macêdo (2022)
Objective: To analyze the incidence, mortality and prostate cancer survival in Cuiabá and Várzea Grande, from 2000 to 2016. Methods: Data from the Population-Based Cancer Registry and the Mortality Information System were used. Mortality and incidence trends analyses were performed using joinpoint regression models by age group. Survival analyses were performed using Kaplan-Meier method and hazard ratio was estimated by age group. Results: From 2000 to 2016, 3,671 new cases and 892 deaths for prostate cancer were recorded. The average incidence and mortality rates were 87.96 and 20.22 per 100,000, respectively. Decreasing incidence trend was noted for all age groups from 2006 to 2016 (APC = -3.2%) and for men with 80+ years of age from 2000 to 2016 (APC = -3.0%), and increasing mortality trend for men 60-69 years of age from 2000 to 2009 (APC = 3.2%). Prostate cancer specific five-year survival rate was 79.6% (CI95%: 77.2; 81.9), and the rate decreased with the advanced age (HR = 2.43, CI95%: 1,5;3,9 for those with 70 to 79 years old and HR = 7.20; CI95%: 4.5;11.5 for those with 80 years old or more). Conclusion: The incidence rate of prostate cancer presented a decreasing trend from 2006, for all age groups, the mortality rate was stable in the period, and worse prognosis was observed in men with 70 years old or more.